Construction of Digital Entrepreneurship with Design Sprint and Social Learning Methods - Andri Irawan (Jurnal Multidisiplin Madani, 2023)
This study aims to increase digital entrepreneurship motivation in students through design sprints and social learning. This research was conducted on 120 student informants who took entrepreneurship lessons from two different campuses in Papua. The research method used is qualitative. Data collection was done by way of interviews and observation. Data analysis using NVivo 12 plus software tools. The results of the study show that design sprints and social learning are very effective as strategies to increase digital entrepreneurship motivation for students. By implementing design sprints and social learning, students can find entrepreneurial ideas faster, are more creative and do not make students bored in class. This research also found opportunities and challenges for students to become digital entrepreneurs such as the lack of digital infrastructure, financial support and geographical conditions. However, there are enormous opportunities for the development of student digital entrepreneurs such as the lack of competitors at the local and regional levels, regional assets such as tourism, agriculture, fisheries and culture which can become digital business opport